Human rights in domestic responses to the COVID-19 pandemic: preliminary findings from a media-coverage database to track human rights violations - Hanna E Huffstetler, BA; Caitlin R Williams, MSPH; Benjamin M Meier, PhD (Elsevier, 2021)
Background: As COVID-19 has spread throughout the world, domestic public health responses have neglected human rights. Human rights are crucial to public health promotion, yet there are significant gaps in how human rights are being monitored during the pandemic response. Existing efforts to track potential human rights violations in domestic responses to COVID-19 are neither comparative nor comprehensive. To fill this gap, we developed a novel, comparative database to systematically track media coverage of potential human rights violations. Using these data, we examine how public health policies impacted human rights realisation across countries during the first 3 months of the pandemic. Methods: We used a systematic qualitative coding methodology to examine the extent and range of media coverage at the intersection of COVID-19, public health, and human rights. Using a structured key-term search strategy, we searched the NexisUni news database for English-language media reports. Results were screened based on pre-determined eligibility criteria, such as whether the report discussed a public health action (or inaction) in response to COVID-19 and described the human rights implications of that action (or inaction). Reports were coded by geographic location, type of public health response, human rights implications, and populations impacted. To guide the coding process, we developed a codebook based on WHO frameworks in public health and UN frameworks in human rights. Findings: In the first 3 months of the pandemic, media coverage of domestic public health responses to COVID-19 increased rapidly as the crisis escalated. This coverage included a wide range of public health actions that impacted human rights across six geographic regions. We identified 17 public health actions that impact 24 distinct human rights, and noted that domestic public health responses were reported to have consequences for the range of civil, political, economic, and social rights that underlie public health. For example, domestic actions to implement lockdown measures were reported to have implications for the human rights to life, liberty and security of person, health, work, and education. These effects were reported to have been experienced differently across national contexts and disproportionately impacted the human rights of particular groups, including women and minority populations. Interpretation: Public health and human rights are inextricably linked in the COVID-19 pandemic. Ongoing data collection and comparative analysis can inform domestic best practices and future pandemic preparedness efforts. Our comparative database provides a foundation for future research that examines the public health impacts of human rights violations in the pandemic response. Funding: None.